Is cytochrome P450 2C9 genotype associated with NSAID gastric ulceration? - Martin, Jennifer H (Blackwell Science Inc, 2001)
AIMS: The aim of this study was to explore whether genetic variation of cytochrome P450 2C9 (CYP2C9) contributes to NSAID-associated gastric ulceration. The hypothesis tested was that CYP2C9 poor metabolizer genotype would predict higher risk of gastric ulceration in patients on NSAIDs that are metabolized by CYP2C9, due to higher plasma NSAID concentrations. METHODS: Peripheral blood DNA samples from 23 people with a history of gastric ulceration attributed to NSAIDs metabolized by CYP2C9, and from 32 people on NSAIDs without gastropathy, were analysed to determine CYP2C9 genotype. RESULTS: The following genotypes were found: *1/*1 (wild type) in 70% of cases and 58% of controls, *1/*2 in 17% of cases and 29% of controls, *1/*3 in 13% of cases and 13% of controls. The difference between case and control nonwild-type genotype frequency was 11.5% (95% CI −14,37%), with the direction of the difference being against the hypothesis. No individuals with homozygote poor metaboliser genotype were identified. The differences in genotype frequencies between the two groups were not significant and the frequencies were similar to those in a large published population study. Ninety-five percent binomial confidence interval analysis confirms that there is no apparent clinically significant relationship between CYP2C9 genotype and risk of gastric ulceration although a small difference in risk in poor metabolizers cannot be excluded. CONCLUSIONS: These results do not support the hypothesis that gastric ulceration resulting from NSAID usage is linked to the poor metabolizing genotypes of CYP2C9.